CONDUCTANCE OF AN ONE AND DOUBLE-LEVEL QUANTUM DOT - GROSU, Ioan (Studia Universitatis Babeș-Bolyai Physica, 2022)
We analytically study the expression of the electric charge current through a two-terminal quantum dot in the linear response approximation. We analyse the one-level and the two-level quantum dot scaled conductance taking into account the relevant parameters. We also present the results for the conductance in the Sommerfeld approximation.